Factors Attributing to Outwards Direct Investments from Developing Countries to Developed Countries: Evidence from China and India - Avina, Diyah Ayu Amalia; Adikara, Henry Kusuma (APMBA (Asia Pacific Management and Business Application), 2016)
The purpose of this research is to explore the growing trend of outward foreign direct investments (OFDIs) from developing countries to developed countries. Market-seeking and strategic asset explorations are the main motivations for conducting OFDIs in developed countries. Meanwhile, cross-border greenfield investments and cross-border mergers and acquisitions are the main entry strategies used by developing countries when penetrating the developed markets. Finally, this paper reveals mixed results about the explaining ability of John Dunning’s International Development Path (IDP) theory on the patterns of selected developing markets' OFDIs to developed countries. On the one hand, China’s OFDIs follow the paths in the IDP theory. On the other hand, those of India do not confirm so.